2006
DOI: 10.1002/joc.1416
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of future climate change in the caribbean region using global general circulation models

Abstract: Abstract:Since the 1800s the global average CO 2 mixing ratio has increased and has been related to increases in surface air temperature (0.6 ± 0.2°C) and variations in precipitation patterns among other weather and climatic variables. The Small Island Developing States (SIDS), according to the 2001 report of the Intergovernmental Panel on Climate Change (IPCC), are likely to be among the most seriously impacted regions on Earth by global climate changes. In this work, three climate change scenarios are invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 24 publications
3
50
0
Order By: Relevance
“…The observed increases in trade winds magnitude have been attributed to an increase in the North Atlantic high [Jury and Winter, 2010;Angeles et al, 2007].…”
Section: Comarazamy and González: Regional And Local Climate Changes mentioning
confidence: 94%
See 1 more Smart Citation
“…The observed increases in trade winds magnitude have been attributed to an increase in the North Atlantic high [Jury and Winter, 2010;Angeles et al, 2007].…”
Section: Comarazamy and González: Regional And Local Climate Changes mentioning
confidence: 94%
“…Figure 6 shows the 1900-2005 SST time series, values are averaged over grid 1. Although there is a general increasing trend of SST in the Caribbean, associated with differences between Caribbean and North Atlantic near-surface pressures [Jury and Winter, 2010;Angeles et al, 2007], there are periods where the increase is more pronounced. These periods are identified as and from the early mid-1970s to 2005; the later period is of great importance for the research presented in this paper because is within the two time frames selected to perform the numerical mesoscale simulations.…”
Section: Large-scale Climate Changesmentioning
confidence: 99%
“…Many of these studies use coarse-resolution general circulation models (GCMs) included in the fourth assessment report (AR4) of the Intergovernmental Panel on Climate Change (IPCC) to describe large-scale climatic changes in the region (e.g., Ángeles et al, 2007;Comarazamy and González, 2008;Biasutti et al, 2012). More recently, a handful of studies have used high-resolution regional climate models (RCMs) for studying climate change and its impact at spatial scales relevant for the islands (e.g., Castro et al, 2006;Centella et al, 2008;Campbell et al, 2010;Charlery and Nurse, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term studies suggest that precipitation has been decreasing in the Caribbean since the 1970s and that droughts in Puerto Rico are periodic [31]. Some studies predict that global warming should result in an increase in negative precipitation anomalies during the summer (June-August), increased dry season duration and more frequent heavy rain events in the Caribbean [14,35,47]. Overall, rainfall in most subtropical areas, including the Caribbean, is projected to decline by around 20% over the next 100 years [36].…”
Section: Previous Precipitation Studies In Puerto Ricomentioning
confidence: 99%
“…Seasonal influence is critically important in the Southeastern Caribbean because most of the precipitation falls during the summer [25]. Simulations with a mesoscale model using the Parallel Climate Model (PCM) to project future climate changes in Puerto Rico under the IPCC's Business as Usual (BAU) Scenario showed that the Southern Oscillation Index (SOI) and NAO have important controls on annual Caribbean rainfall variability [47]. [25] Effects are based on observations unless otherwise indicated;…”
Section: Subregional Precipitation Zones and The Impacts Of Enso And Naomentioning
confidence: 99%